The chromosome-level draft genome of Dalbergia odorifera. Issue 8 (18th August 2020) - Hong, Zhou; Li, Jiang; Liu, Xiaojin; Lian, Jinmin; Zhang, Ningnan; Yang, Zengjiang; Niu, Yongchao; Cui, Zhiyi; Xu, Daping
Abstract: Background: Dalbergia odorifera T. Chen (Fabaceae) is an International Union for Conservation of Nature red-listed tree. This tree is of high medicinal and commercial value owing to its officinal, insect-proof, durable heartwood. However, there is a lack of genome reference, which has hindered development of studies on the heartwood formation. Findings: We presented the first chromosome-scale genome assembly of D. odorifera obtained on the basis of Illumina paired-end sequencing, Pacific Biosciences single-molecule real-time sequencing, 10x Genomics linked reads, and Hi-C technology. We assembled 97.68% of the 653.45 Mb D. odorifer a genome with scaffold N50 and contig sizes of 56.16 and 5.92 Mb, respectively. Ten super-scaffolds corresponding to the 10 chromosomes were assembled, with the longest scaffold reaching 79.61 Mb. Repetitive elements account for 54.17% of the genome, and 30, 310 protein-coding genes were predicted from the genome, of which ∼92.6% were functionally annotated. The phylogenetic tree showed that D. odorifera diverged from the ancestor of Arabidopsis thaliana and Populus trichocarpa and then separated from Glycine max and Cajanus cajan . Conclusions: We sequence and reveal the first chromosome-level de novo genome of D. odorifera . These studies provide valuable genomic resources for the research of heartwood formation in D. odorifera and other timber trees. The high-quality assembled genome can also be used as reference for comparative genomics analysis and future population genetic studies of D. odorifera .